To Be or Not to Be Human: Human Enhancement – an Eternal Temptation - Scarnecchia, Brian (Chrześcijaństwo-Świat-Polityka, 2025)
Exploring the architecture of the human mind manifest in storytelling, J.R.R. Tolkien noted that “the great mythical significance of prohibition” cast in fairy-story is depicted as “The Locked Door” which “stands as an eternal Temptation.” This article asks – do human enhancement technologies tempt us to ignore a prohibition seemingly universal and somehow innate, an eternal Temptation, urging us to pry open the Locked door, a closed garden, and eat a forbidden fruit that promises to lift the strictures of human nature? This article presents an overview of the basic characteristics of human enhancement and applies ethical principles drawn from Catholic social teaching to the legal and public policy controversies surrounding genetic and physical human enhancement technologies as well as the patent eligibility of human DNA segments. I argue that human enhancement technologies that assist but do not replace integral human nature contribute to human ecology while those that tempt us to go beyond the bounds of human nature contribute to a new eugenics.